Digital Competence and Teacher Preparedness for Educational Transformation in the Merdeka Curriculum Framework - Moh Masnun; Patimah Patimah; Aceng Jaelani; Dia Penata Candawati (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractThis research aims to analyze the digital competency level of teachers at Madrasah Ibtidaiyah (MI) in Cirebon Regency, West Java, Indonesia. The research methodology employs a mixed-method approach, combining quantitative and qualitative methods. 49 MI teachers were selected as respondents through random sampling techniques. Data collection was conducted through questionnaires and in-depth interviews. Descriptive statistics were used to look at quantitative data, and data reduction, data presentation, and conclusion drawing were used to look at qualitative data. Findings show a generally low level of digital competence, with a mean score of 2.28 (SD = 0.86) on a 5-point scale. Most teachers (40.8%) fell into the “Low” category, 30.6% were “Moderate,” and only 4.1% achieved “Very High.” Digital communication had the highest score (M = 2.52), followed by technology use (M = 2.42), digital ethics (M = 2.11), and content creation (M = 2.08). Teachers struggled most with creating digital materials, using online platforms, and understanding digital ethics. Teaching experience (F = 2.49, p = 0.045) and school location (F = 3.26, p = 0.047) showed significant differences, with urban and less-experienced teachers performing better. The regression analysis revealed age, teaching experience, rural location, and prior training as significant predictors, accounting for 43.5% of the variance. There were no differences between the sexes. The implications of this research point to the urgency of implementing programs to enhance teachers' digital competency. More broadly, this research impacts educational policy formulation, curriculum development, and the transformation of Islamic education in facing the digital era.Keywords: digital competency, islamic education, teacher development. AbstrakPenelitian ini bertujuan untuk menganalisis tingkat kompetensi digital guru di Madrasah Ibtidaiyah (MI) di Kabupaten Cirebon, Jawa Barat, Indonesia. Metode penelitian menggunakan pendekatan metode campuran, menggabungkan metode kuantitatif dan kualitatif. 49 guru MI dipilih sebagai responden melalui teknik pengambilan sampel acak. Pengumpulan data dilakukan melalui kuesioner dan wawancara mendalam. Statistik deskriptif digunakan untuk melihat data kuantitatif, dan reduksi data, penyajian data, dan penarikan kesimpulan digunakan untuk melihat data kualitatif. Temuan menunjukkan tingkat kompetensi digital yang umumnya rendah, dengan skor rata-rata 2,28 (SD = 0,86) pada skala 5 poin. Sebagian besar guru (40,8%) termasuk dalam kategori